2021
DOI: 10.3892/etm.2021.9760
|View full text |Cite
|
Sign up to set email alerts
|

Short‑chain fatty acid butyrate: A novel shield against chronic gastric ulcer

Abstract: Butyrate is one of the most abundant short-chain fatty acids produced by intestinal bacteria. In the present study, the action of butyrate on chronic gastric mucosa lesions was investigated, as well as its underlying mechanism in mice. Male mice from the Institute of Cancer Research were randomly divided into three groups: Sham, model and butyrate groups. Butyrate was administered intragastrically for 7 days to butyrate group mice following the establishment of a gastric ulcer model. Hematoxylin and eosin stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, in our study, butyrate was only effective in reducing CXCL1 and CXCL2 expression, while it was propionate that demonstrated attenuation of the IL1β- and TNFα-induced expression of IL8, CXCL1, and CXCL2 in HSC2 cells. Nevertheless, our data are consistent with findings that butyrate attenuates the excessive inflammation involved in the development of gastric mucosal ulcers induced by erosion due to acid in mice [ 54 ] and that butyrate inhibits LPS-induced cytokine production in mammary epithelial cells [ 55 ]. Butyrate further decreased TNFα-induced IL8 and CXCL2 expression in endothelial cells [ 56 , 57 ] and IL8 in the intestinal jejunal epithelial cell line J2 exposed to LPS [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in our study, butyrate was only effective in reducing CXCL1 and CXCL2 expression, while it was propionate that demonstrated attenuation of the IL1β- and TNFα-induced expression of IL8, CXCL1, and CXCL2 in HSC2 cells. Nevertheless, our data are consistent with findings that butyrate attenuates the excessive inflammation involved in the development of gastric mucosal ulcers induced by erosion due to acid in mice [ 54 ] and that butyrate inhibits LPS-induced cytokine production in mammary epithelial cells [ 55 ]. Butyrate further decreased TNFα-induced IL8 and CXCL2 expression in endothelial cells [ 56 , 57 ] and IL8 in the intestinal jejunal epithelial cell line J2 exposed to LPS [ 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…One hypothesis is that S. boulardii can influence immunological function by enhancing the synthesis of short-chain fatty acids, including butyrate [23]. This is of interest as butyrate may aid in the repair of the gastric mucosa due to its anti-oxidative and anti-inflammatory properties [24]. In addition, animal studies have demonstrated that E. faecium may exert an immunomodulatory function [25].…”
Section: Discussionmentioning
confidence: 99%
“…Undigested carbohydrates are fermented by the gut microbiota into the SCFA acetate, propionate, and butyrate, which are beneficial to reducing inflammation, enhancing immunity and stimulating epithelial cell growth for the host [Macfarlane and Macfarlane, 2012]. Especially, SCFA butyrate has anti‐inflammatory and anti‐oxidative effects and improves gut barrier function, thus playing a role in oxidative stress in the healthy colonic mucosa [Hamer et al, 2009; Hamer et al, 2010; Zhou et al, 2021]. In this study, the trend of decreased butyrate in HMF‐exposed mice may attenuate its role in anti‐inflammatory and antioxidant effects in the colon.…”
Section: Discussionmentioning
confidence: 99%